1984
DOI: 10.1093/ajcp/81.5.569
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Secretory IgA in Serum by Radioimmunoassay in Patients with Chronic Nonalcoholic Liver Disease or Carcinoma

Abstract: The authors describe the development of a double antibody radioimmunoassay specific for human secretory IgA (sIgA), and they report the results of measurements of serum sIgA concentrations in patients with chronic, nonalcoholic liver disease or carcinoma. Above-normal sIgA concentrations (greater than 25 micrograms/mL) were found in 22 of 38 sera from patients with chronic active liver disease and in 37 of 40 sera from patients with primary biliary cirrhosis. Markedly increased concentrations (greater than 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…2). Similar observations were made in hepatic tumors: we demonstrated the presence of high levels of S-IgA, S-IgM and free-SC in South African patients with primary hepatic carcinoma [68], A similar increase of S-IgA has been described in hepatic métastasés of epithelial tumors [66,69], This increase has even been proposed as a marker of liver metastases in the follow-up of patients with carcinoma, and explained by a synthesis and release of SC by the neoplastic epithelial cells [66]. However, we did not find any expression of SC in tumoral cells, in primary as well as in secondary carcinomas: SC was present only in duct-like cells at the periphery of the tumor [Rossel et al, unpubl.…”
Section: Iga In Acute Liver Necrosis (Acute and Fulminant Hepatitis)supporting
confidence: 88%
See 1 more Smart Citation
“…2). Similar observations were made in hepatic tumors: we demonstrated the presence of high levels of S-IgA, S-IgM and free-SC in South African patients with primary hepatic carcinoma [68], A similar increase of S-IgA has been described in hepatic métastasés of epithelial tumors [66,69], This increase has even been proposed as a marker of liver metastases in the follow-up of patients with carcinoma, and explained by a synthesis and release of SC by the neoplastic epithelial cells [66]. However, we did not find any expression of SC in tumoral cells, in primary as well as in secondary carcinomas: SC was present only in duct-like cells at the periphery of the tumor [Rossel et al, unpubl.…”
Section: Iga In Acute Liver Necrosis (Acute and Fulminant Hepatitis)supporting
confidence: 88%
“…The IgAl/IgA2 ratio is also normal [46]. In fact in most diseases characterized by chole stasis, the major -and often isolated -alter ation in serum IgA consists in a marked increase in S-IgA [46,61,66,67], Very high levels of serum S-IgA have even been pro posed as a new biological marker of PBC [66]. Results of many studies dealing with various forms of LD have proven its lack of specificity, particularly among cholestatic diseases [46.…”
Section: Iga In Acute Liver Necrosis (Acute and Fulminant Hepatitis)mentioning
confidence: 99%
“…Previous reports have considered SC as a marker for colorectal carcinomas, both in terms of its cytoplasmic expression in tumours (Poger et al, 1976;Rognum et al, 1982;Arends et al, 1984;Brooks & Ernst, 1984) and its appearance in peripheral blood (Homburger et al, 1984;Kvale et al, 1987a). However, tumour expression and the corresponding serum levels of SC in patients with colorectal (Kvale et al, 1987a) and breast (Kvale et al, 1987c) carcinomas are not correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed elevations of serum SC were most likely explained by secondary changes in the liver. Various liver diseases may likewise cause increased serum levels of SIgA (Delacroix et al, 1983;Homburger et al, 1984;Kvale et al, 1987b) and/or SIgM (Kvale et al, 1987b). However, the pathophysiological alterations underlying the increases observed in association with liver metastases are obscure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SC is present in serum bound to both p-IgA and IgM in a proportion related to the serum p-IgA/IgM molar ratio (6). Increased S-IgA and S-IgM have been detected in the serum of patients with chronic liver diseases, using various techniques (14,19). We have shown that very elevated concentrations of Ir F-SC are to be found in the serum of patients with HCC (7).…”
Section: Discussionmentioning
confidence: 99%